Capturing Changes in Social Media Content: A Multiple Latent Changepoint Topic Model - Zhong, Ning; Schweidel, David A. (Marketing Science, 2020)
We develop a topic model with multiple latent changepoints and demonstrate an approach to detect changes in the topics mentioned in brand-related social media posts.